The fuller memorandum eaudiobook - Stross, Charles (Laundry Files, 2011)
Hugo Award-winning author Charles Stross is renowned for his cutting-edge science fiction. This third entry in his "edgy . spoof of Cold War spy thrillers" (Booklist) finds covert agent Bob Howard learning about a top-secret dossier that vanishes with his boss. Determined to discover the contents of this memorandum, Howard runs afoul of Russian spies, ancient demons, and apostles of a hideous cult planning to raise the Eater of Souls from the undead.